Cervical amyloidoma of transthyretin type: a case report and review of literature - Matthew H. MacLennan; André le Roux (BMC Geriatrics, 2022)
Abstract Background Amyloidoma is a rare clinical entity characterized by the focal aggregation of amyloid protein within the body, void of systemic involvement. To our knowledge, there have only been 26 reports of cervical amyloidoma to date. Amyloid light chain and beta-2-microglobulin are the most common types, with only three previous reports of transthyretin (ATTR) Amyloidoma. Case presentation We report a case of a 71-year-old male who presented with worsening strength and coordination of his upper extremities, right upper-leg pain, unsteady gait, and a reduced range of motion of his neck in all planes. Magnetic resonance imaging revealed a solitary mass compressing the spinal cord at C1-C2. Treatment consisted of cervical decompression and stabilization. Pathological examination confirmed solitary amyloid deposition of ATTR. Postoperative neurological assessment revealed improved balance, gait, hand function, and grip strength. Investigational imaging was ordered 8 months postoperatively revealing no evidence of systemic involvement, confirming the diagnosis of cervical ATTR amyloidoma. A discussion is provided surrounding the published literature of ATTR amyloidoma with description of the typical presentation, management, and outcomes of this rare pathology. Conclusion Previous cases and studies indicate clinical signs such as ligamentum of flavum hypertrophy and carpal tunnel syndrome may precede focal ATTR spinal disposition. Outcomes for amyloidoma are generally favourable, as tumour resection prevents irreversible deficits. Patients have a low rate of recurrence with an overall excellent prognosis following resection and stabilization.